2004
DOI: 10.1007/s10067-004-1024-2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus arising during interferon-alpha therapy for cryoglobulinemic vasculitis associated with hepatitis C

Abstract: We present the case of a 53-year-old woman who developed systemic lupus erythematosus (SLE) after being treated with interferon-alpha (IFN-alpha) for cryoglobulinemic vasculitis associated with hepatitis C virus (HCV) infection. Her cryoglobulinemic vasculitis resolved rapidly with IFN-alpha treatment. However, after 10 months of IFN-alpha therapy, she developed a photosensitive malar rash, oral ulcers, arthralgias, lymphopenia, and anti-SSA autoantibodies. She was diagnosed with SLE induced by IFN-alpha thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 13 publications
2
109
0
Order By: Relevance
“…IFN-a-based treatments are widely used for viral hepatitis and carcinoid tumors; however, several case reports have emerged describing autoimmune conditions that have developed during IFN-a therapy. [13][14][15] These observations in human and murine lupus implicate a complicated role of the type I IFN involved in lupus pathogenesis. We hypothesize that inappropriate activation of type I interferon (IFN) signaling pathways, combined with a genetic predisposition, may be important in SLE pathogenesis.…”
Section: Introductionmentioning
confidence: 93%
“…IFN-a-based treatments are widely used for viral hepatitis and carcinoid tumors; however, several case reports have emerged describing autoimmune conditions that have developed during IFN-a therapy. [13][14][15] These observations in human and murine lupus implicate a complicated role of the type I IFN involved in lupus pathogenesis. We hypothesize that inappropriate activation of type I interferon (IFN) signaling pathways, combined with a genetic predisposition, may be important in SLE pathogenesis.…”
Section: Introductionmentioning
confidence: 93%
“…2,3 Additionally, a number of patients treated with recombinant human IFN-a for malignancy and chronic viral hepatitis have developed de novo SLE, which typically resolves after the IFN-a is discontinued. 4,5 Our group and others have shown that SLE patients exhibit coordinate overexpression of IFN-ainduced genes in their peripheral blood mononuclear cells (PBMCs) as compared with healthy individuals and patients with other inflammatory diseases such as rheumatoid arthritis. [6][7][8] Increased IFN-a-induced gene expression correlates with greater disease activity and particular autoantibody profiles and disease phenotypes in SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the effect of INF-in SLE comes from observations on the therapeutic administration of IFN-in various types of malignancies and hepatitis C infection. Case reports emerged describing the development of lupus associated autoantibodies and even clinical lupus (Niewold & Swedler 2005). Discontinuation of IFN-α typically resulted in remission of SLE symptoms, supporting a causal relationship with IFN-α.…”
Section: Interferon-αmentioning
confidence: 96%